EMERGENCY AND INITIAL GROWTH OF WATERMELON UNDER SALT STRESS - RIBEIRO, Aureliano de Albuquerque; SALES, Mariana Alexandre de Lima; ELOI, Waleska Martins; MOREIRA, Francisco José Carvalho; SALES, Francisco Alexandre de Lima (Revista Brasileira de Engenharia de Biossistemas, 2012)
The present study evaluated the effect of different salinity levels (0.17; 1.5; 2.5; 3.5; 4.5 and 5.5 dSm-1) of irrigation water in emergence and early growth watermelon Crimson Sweet. The experiment was conducted under laboratory conditions and field at the Instituto Federal de Educação, Ciência e Tecnologia - IFCE, Campus de Sobral. We used the full experimental design (DIC) with four replications, placing 32 seeds per experimental unit. The variables analyzed were in emergency: first count, emergence percentage and emergence rate index (IVE); initial growth: seedling height, stem diameter, number of leaves, dry weight of shoot and root. Salt stress produced a negative effect on both emergency as early growth Watermelon Crimson Sweet, however, during the emergency reductions were smaller, showing greater tolerance to salinity of the culture at this stage.